The Seventeenth-century resolve a historical anthology of a literary form - Lievsay, John Leon. (Lexington : The University Press of Kentucky, 2015)
Popular in its time, the resolve is now almost forgotten. In this anthology John L. Lievsay has gathered a representative collection of resolves and has provided also a critical history of the genre -- its flowering and decline.
Cover; Title; Copyright; Contents; PREFACE; INTRODUCTION; JOSEPH HALL Meditations and Vowes Divine and Morall; DANIEL TUVILL Christian Purposes and Resolutions; ANTHONY STAFFORD Meditations and Resolutions, Moral, Divine, Politicall; THOMAS TUKE New Essayes: Meditations and Vowes; NICHOLAS BRETON I Would and Would Not; FRANCIS ROUS Meditations of Instruction, of Exhortation, of Reproofe; RICHARD BRATHWAIT Essaies upon the Five Senses; OWEN FELTHAM Resolves. A Duple Century; WILLIAM STRUTHER Christian Observations and Resolutions; JOSEPH HENSHAW Horae Succisivae, or Spare-houres of Meditations.
Includes bibliographical references and index.
Print version record.
Keywords: English prose literature -- Early modern, 1500-1700.; English prose literature; Meditations; RELIGION -- Christian Life -- Devotional; RELIGION -- Devotional; Meditations; English prose literature -- Early modern, 1500-1700.; Electronic books